A novel exposure system generating nebulized aerosol of sulfur mustard in comparison to the standard submerse exposure. (25th January 2019) - Tsoutsoulopoulos, Amelie; Siegert, Markus; John, Harald; Zubel, Tabea; Mangerich, Aswin; Schmidt, Annette; Mückter, Harald; Gudermann, Thomas; Thiermann, Horst; Steinritz, Dirk; Popp, Tanja
Abstract: Inhalation of the chemical warfare agent sulfur mustard (SM) is associated with severe acute and long-term pulmonary dysfunctions and health effects. The still not completely elucidated molecular toxicology and a missing targeted therapy emphasize the need for further research. However, appropriate human data are extremely rare. In vivo animal experiments are often regarded as gold standard in toxicology but may exhibit significant differences compared to the human pulmonary anatomy and physiology. Thus, alternative in vitro exposure methods, adapted to the human in vivo situation by exposing cells at the air-liquid interface (ALI), are complimentary approaches at a cellular level. So far, it is unclear whether the enhanced experimental complexity of ALI exposure, that is potentially biologically more meaningful, is superior to submerged exposures which are typically performed. Aim of our study was the evaluation of an appropriate in vitro exposure system (CULTEX ® Radial Flow System (RFS) equipped with an eFlow ® membrane nebulizer) for the exposure of cultivated human lung cells (A549) with SM under ALI conditions. Cellular responses (i.e. cell viability) and formation of SM-specific DNA-adducts were investigated and compared between ALI and submerse SM exposures. Our results proved the safe applicability of our ALI exposure system setup. The aerosol generation and subsequent deposition at the ALI were stable and uniform. The technical CULTEX ® RFS setup is based on ALI exposure with excess of aerosol from that only some is deposited on the cell layer. As expected, a lower cytotoxicity and DNA-adduct formation were detected when identical SM concentrations were used compared to experiments under submerged conditions. A distinct advantage of SM-ALI compared to SM-submerse exposures could not be found in our experiments. Though, the CULTEX ® RFS was found suitable for SM-ALI exposures. Highlights: The CULTEX ® RFS was modified and evaluated for nebulized SM exposure. Exposures of A549 cells to SM was compared to submerse and air-liquid interface (ALI) conditions. A homogenous distribution of SM DNA-adducts was observed in both groups. Significant differences regarding cell viability were evident. A direct comparison of ALI and submerse exposure conditions is challenging.